Pharmacokinetic of gabapentin 600 mg tablet in Thai healthy subjects - Wittayalertpanya, Supeecha; Chompootaweep, Sumana; Thaworn, Nongnuch; Khemsri, Wondee; Prompila, Nantaporn; Sayankuldilok, Nonlanee; Punyasang, Wasan (Journal of the Medical Association of Thailand, 2012)
Gabapentin is an antiepileptic drug. It is structurally similar to yaminobutyric acid (GABA), which crosses the blood-brain barrier. Gabapentin is absorbed into the blood by the L-amino acid transport system. The oral bioavailability of gabapentin displays dose-dependence. Plasma concentrations ofgabapentin are not directly proportional to dose. Therefore, pharmacokinetic of gabapentin is essential for patients who have to receive gabapentin 600 mg. To investigate the pharmacokinetic of gabapentin 600 mg in Thai healthy subjects. The present study was performed on 24 healthy Thai male subjects who received a single oral dose of 600 mg gabapentin tablet. Serial blood samples were collected before and to 48 hours after drug administration. Plasma gabapentin concentrations were determined by automated High Performance Liquid Chromatography (HPLC) with UV detector after deproteinized with acetonitrile followed by derivatization with 1-fluoro-2,4-dinitrobenzene. The relevant pharmacokinetic parameters were determined. The mean values of pharmacokinetic parameters (mean +/- SD) were 3.17 +/- 0.80 hour (1.5 to 5.0 hour) for T; 4,853.58 +/- 1,369.67 ng/ml for Cm; 0.11 +/- 0.02 hour for Kel, 6.62 +/- 1.87 hour (4.89 to 11.41 hour) for T1/2; 47,712.88 +/- 12,853.61 ng.hour/ml for AUC0-t, 48,713.20 +/- 12,909.78 ng.hour/ml for AUC0-inf, 5.24 +/- 1.32 L/hour for CI, and 49.28 +/- 15.98 L for Vd. The data show the pharmacokinetic parameters of gabapentin 600 mg. These data should be used to support the assignment of therapeutic purposes for patients who have to receive gabapentin 600 mg.